2022
DOI: 10.1088/1361-648x/aca3eb
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial strain improving carrier mobility for inorganic perovskite: ab initio Boltzmann transport equation

Abstract: Inorganic halide perovskites have attracted interest due to their high efficiency and low cost. Considering the uncertainty of ex perimental measurements, it was important to predict the upper limit of carrier mobility. In this study, the ab initio Boltzmann transport equation (BTE), including all electron-phonon interactions, was used to accurately predict the mobilities of CsPbI3, CsSnI3, CsPbBr3, and CsSnBr3. Using the iterative Boltzmann transport equation (IBTE), the calculated mobility for CsPbI3 is µe=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 102 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…The calculations showed that the electron mobility of these four β-AMO 2 candidate IFSs was in the range of 9 × 10 3 to 3.7 × 10 5 cm s −1 V −1 and the hole mobility was up to 1.7 × 10 3 cm s −1 V −1 compared with other types of photocatalysts, such as inorganic chalcogenides (9 × 10 2 –10 3 cm s −1 V −1 ), 82 inorganic–organic chalcogenides (7–30 × 10 3 cm s −1 V −1 ), 83 and heterojunction structures (104 cm s −1 V −1 ), 84 indicating the excellent catalytic performance of these ferroelectric photocatalysts.…”
Section: Resultsmentioning
confidence: 93%
“…The calculations showed that the electron mobility of these four β-AMO 2 candidate IFSs was in the range of 9 × 10 3 to 3.7 × 10 5 cm s −1 V −1 and the hole mobility was up to 1.7 × 10 3 cm s −1 V −1 compared with other types of photocatalysts, such as inorganic chalcogenides (9 × 10 2 –10 3 cm s −1 V −1 ), 82 inorganic–organic chalcogenides (7–30 × 10 3 cm s −1 V −1 ), 83 and heterojunction structures (104 cm s −1 V −1 ), 84 indicating the excellent catalytic performance of these ferroelectric photocatalysts.…”
Section: Resultsmentioning
confidence: 93%
“…The mechanical behavior of these perovskites was mainly determined by the interaction between B-site cations and halogen anions. 49,64 Due to electronegativity and ionic radius, the bond characteristics between group II and halogen were different from those between group IV and halogen. In the xy plane, the bond angle was 160.7° for Cl–Sn–Cl, 153.9° for Cl–Sr–Cl, 173.9° for Cl–Ca–Cl, 179.9° for Cl–Mg–Cl and Br–Mg–Br, and 168.2° for I–Mg−I, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It satisfied J e, α = neμ e, αβ E β , where n denotes the number of electrons per unit volume and μ e denotes the carrier mobility. If the current density satisfied a linear response under the action of an electric field, the mobility could be expressed as follows: 36,63,64 Here, the carrier group velocity could be obtained by taking the first derivative of the energy band, expressed as v n k , α = ħ −1 ∂ E n k /∂ k α , where E n k is the carrier energy at n band with a wave vector of k . f n k is the Fermi–Dirac distribution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation